2001
DOI: 10.1016/s0014-5793(01)02160-3
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone inhibits osteoclast formation stimulated by parathyroid hormone through androgen receptor

Abstract: Androgens play an important role in the regulation of bone metabolism in animals and humans. The present study was performed to investigate whether androgens would affect osteoclast formation stimulated by parathyroid hormone (PTH) in mouse bone cell cultures and its mechanism. Testosterone as well as K K-dihydrotestosterone (DHT) concentration-dependently inhibited osteoclast formation induced by PTH-(1-34). 10 38 M ICI 182780, an estrogen receptor inhibitor, did not affect PTHinduced osteoclast formation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 25 publications
3
46
0
Order By: Relevance
“…Interestingly, the global AR null model also develops late onset obesity [15]. Finally, recent publications document that androgen can directly reduce bone resorption of isolated osteoclasts [45], inhibits osteoclast formation stimulated by PTH [10], and may play a direct role regulating aspects of osteoclast activity in conditional AR null mice [40]. Our results suggest that at least some component of inhibition of osteoclastic resorptive activity as a consequence of androgen administration is mediated indirectly through effects on mature osteoblasts and osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the global AR null model also develops late onset obesity [15]. Finally, recent publications document that androgen can directly reduce bone resorption of isolated osteoclasts [45], inhibits osteoclast formation stimulated by PTH [10], and may play a direct role regulating aspects of osteoclast activity in conditional AR null mice [40]. Our results suggest that at least some component of inhibition of osteoclastic resorptive activity as a consequence of androgen administration is mediated indirectly through effects on mature osteoblasts and osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Normal male rats have androgens like testosterone, dihydrotestosterone (DHT) and non-aromatizable androgens which were able to suppress the osteoclast formation (33) and increase the osteoblast proliferation to maintain bone density (34,35). The protective role of androgens in bone regulation was supported by other studies (36,37,38,39). Estrogen was also shown to play an important role in maintaining the bone density in males (40).…”
Section: Discussionmentioning
confidence: 94%
“…Numerous in vitro, in vivo and human clinical studies have evidenced the substantial anti-osteoporotic efficacy of 5α-DHT and their roles in the regulation of skeletal homeostasis [15][16][17][18][19][20]. Chen et al [17] demonstrated that 5α-DHT inhibits osteoclast formation, differentiation and maturation by blocking androgen receptors. The involvement and prime importance of androgen receptors and estrogen receptors has also been critically discussed by Mohamed et al [21].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have evidenced the substantial roles of androgens (dihydrotestosterone) in the regulation of skeletal homeostasis in humans [15,16] and rodents [17][18][19][20]. According to a recently published review [21], testosterone imparts promising roles in improving the bone health by enhancing the proliferation and differentiation of osteoblasts and down-regulating the maturation of osteoclasts.…”
Section: Introductionmentioning
confidence: 99%